2019
DOI: 10.1080/16522354.2019.1641672
|View full text |Cite
|
Sign up to set email alerts
|

The practice of shared inquiry: how actors manageforstrategy emergence

Abstract: This paper problematizes the applicability of traditional top-down strategic planning in a continuously changing media industry and builds a practice-theoretical perspective for analyzing strategy emergence. Through a qualitative analysis of 22 interviews, with media professionals and consultants of a German-based print magazine company, we identify a jointly enacted practice that we call "shared inquiry". This practice includes recursive and adaptive strategizing actions towards (1) searching and learning (ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 112 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Different business models utilizing digital technologies are now emerging in the commerce, entertainment, and media sectors and are demonstrating success with financing, trust, and privacy. This gives us an opportunity to discuss how these business models can be adopted and best translated into health settings [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different business models utilizing digital technologies are now emerging in the commerce, entertainment, and media sectors and are demonstrating success with financing, trust, and privacy. This gives us an opportunity to discuss how these business models can be adopted and best translated into health settings [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the three critical practices of writing, casting, and editing entered an arena of collective reflexivity. In the wider media industry, including publishing, managers and creative professionals increasingly need to "share inquiry" and absorb complex interactions of actors, emotions, technologies, and tools to better prepare for change and uncertainty in the industry (Horst et al, 2019;Virta and Malmelin, 2017).…”
Section: Powermentioning
confidence: 99%
“…The production process became an improvisational struggle, but the authors reported that the practices on the set were characterized by an implicit “negotiated order.” Although the broadcaster had control of the production through its commission apparatus, the power distributions were characterized as “soft.” Accordingly, the three critical practices of writing, casting, and editing entered an arena of collective reflexivity. In the wider media industry, including publishing, managers and creative professionals increasingly need to “share inquiry” and absorb complex interactions of actors, emotions, technologies, and tools to better prepare for change and uncertainty in the industry (Horst et al., 2019; Virta and Malmelin, 2017).…”
Section: Powermentioning
confidence: 99%
“…When studying strategy practices, the focus is on the doings and sayings of strategy practitioners (Horst, Järventie-Thesleff, & Baumann, 2019). In this study, we see strategy as a reflective practice that emerges in the mediatised interaction with potential customers and other stakeholders over time.…”
Section: Practices Of Mediatised Interactionmentioning
confidence: 99%